How effective are central counterparties for risk reduction? - Wildauer, Rafael (Momentum Quarterly, 2012)
With the financial crisis of 2007/08 an active discussion on financial market regulation and especially on regulation of over the counter traded (OTC) derivative markets emerged. The concept of central counterparty clearing (CCP) as a measure to reduce systemic risk is central to this debate. The purpose of this article is to discuss the basic functioning of OTC derivatives markets as well as the potential problems regulators are confronted with when introducing CCP clearing. The article concludes with a short overview of the current legal situation of OTC market regulations in Europe.
Keywords: over the counter derivatives; central counterparties; counterparty risk